REFLEKSI NILAI ADAB DAN HUBUNGAN HORIZONTAL DALAM NASKAH BABAD AWAK SALIRA - Isep Bayu Arisandi; Titin Nurhayati Ma’mun; Undang Ahmad Darsa (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2021)
ABSTRACT The value of moral affects the horizontal relationship that exists between humans. This is recorded in the ancient texts of the Islamic period as evidence of the influence of Islamic teachings that entered the archipelago. The disclosure of this moral value is an effort to